Biocompatibility of Dextran-Coated 30 nm and 80 nm Sized SPIONs towards Monocytes, Dendritic Cells and Lymphocytes - Zschiesche, Lisa; Janko, Christina; Friedrich, Bernhard; Frey, Benjamin; Band, Julia; Lyer, Stefan; Alexiou, Christoph; Unterweger, Harald (Nanomaterials, 2023)
Dextran-coated superparamagnetic iron oxide nanoparticles (SPIONDex) of various sizes can be used as contrast agents in magnetic resonance imaging (MRI) of different tissues, e.g., liver or atherosclerotic plaques, after intravenous injection. In previous studies, the blood compatibility and the absence of immunogenicity of SPIONDex was demonstrated. The investigation of the interference of SPIONDex with stimulated immune cell activation is the aim of this study. For this purpose, sterile and endotoxin-free SPIONDex with different hydrodynamic sizes (30 and 80 nm) were investigated for their effect on monocytes, dendritic cells (DC) and lymphocytes in concentrations up to 200 µg/mL, which would be administered for use as an imaging agent. The cells were analyzed using flow cytometry and brightfield microscopy. We found that SPIONDex were hardly taken up by THP-1 monocytes and did not reduce cell viability. In the presence of SPIONDex, the phagocytosis of zymosan and E. coli by THP-1 was dose-dependently reduced. SPIONDex neither induced the maturation of DCs nor interfered with their stimulated maturation. The particles did not induce lymphocyte proliferation or interfere with lymphocyte proliferation after stimulation. Since SPIONDex rapidly distribute via the blood circulation in vivo, high concentrations were only reached locally at the injection site immediately after application and only for a very limited time. Thus, SPIONDex can be considered immune compatible in doses required for use as an MRI contrast agent.
CRIS-Team Scopus Importer:2023-01-20
Keywords: biocompatibility; immune response; magnetic resonance imaging (MRI); nanomedicine; superparamagnetic iron oxide nanoparticles (SPION)